New species, notes and record of New World Acanthocinini (Coleoptera: Cerambycidae, Lamiinae) - Santos-Silva, Antonio; Bezark, Larry G. (Zootaxa, 2024)
Comments on Leptostylus LeConte, 1852, Pseudastylopsis Dillon, 1956, and Sternacutus Gilmour, 1961 are provided. Four new species and one new genus are described: Lepstotylus arcuatus sp. nov., from Costa Rica; Pseudastylopsis morrisi sp. nov., from Honduras; Quissunego confusus, gen. nov., sp. nov., from Bolivia; and Sternacutus similis sp. nov., from Bolivia. Leptostylus scudderi Wickham, 1914 is transferred to incertae sedis in Acanthocinini. A new regional record is provided for Neopalame albomaculata Monné & Martins, 1976.